2014
DOI: 10.1016/j.bbmt.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefit of Bortezomib on Acute Graft-versus-Host Disease Is Tissue Specific and Is Associated with Interleukin-6 Levels

Abstract: Bortezomib, a proteasome inhibitor capable of direct anti-tumor effects, has been shown to prevent acute graft-versus-host disease (aGVHD) when administered in a short course immediately after bone marrow transplantation (BMT) in mice. However, when given continuously, CD4+ T cell mediated gastrointestinal tract damages increase GVHD mortality. To investigate the protective effects of bortezomib on other organs, we have used a CD8 dependent aGVHD model of C3H.SW donor T cells engrafted into irradiated C57BL/6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…Organ-specific effects may be associated with the effects of neddylation pathways on donor T cells, particularly on chemokine receptor expression. We previously showed that inhibiting proteasome in T cell subsets with bortezomib can decrease CXCR3 expression on T cells [27], and CXCR3 has been shown to affect skin homing. Therefore, it is possible that neddylation also can affect the expression of chemokine receptors, resulting in organ-specific protection effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organ-specific effects may be associated with the effects of neddylation pathways on donor T cells, particularly on chemokine receptor expression. We previously showed that inhibiting proteasome in T cell subsets with bortezomib can decrease CXCR3 expression on T cells [27], and CXCR3 has been shown to affect skin homing. Therefore, it is possible that neddylation also can affect the expression of chemokine receptors, resulting in organ-specific protection effects.…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib is known to preferentially provide therapeutic effects in the skin, but not in the liver or GI tract [9,27]. We tested pevonedistat in a small range of dosages (data not shown), and the dosages and administration schedule need to be carefully evaluated for translation into clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, beneficial effects of proteasome inhibition on the prevention and treatment of acute and chronic GVHD (Li et al, 2013;Herrera et al, 2014;Pai et al, 2014aPai et al, ,2014b, and the growing knowledge of its anti-cancer effects in lymphoid B and T cell malignancies warrants expanded exploration of using bortezomib as well as next generation proteasome inhibitors in this field. We believe bortezomib to be the cause of the patient's rapidly recovered haemoglobin and feel this is a promising, well tolerated regimen which may benefit others in refractory red cell aplasia following ABO mismatched allo-HCT.…”
Section: Successful Treatment Of Refractory Pure Red Cell Aplasia Witmentioning
confidence: 98%
“…Pre-clinical mouse work with the FDA-approved proteasome inhibitor bortezomib demonstrated that it is a potent inhibitor of alloreactive T cells, and that bortezomib treatment reduced acute GVHD without affecting GVT (50, 51). In addition, one of the mechanisms by which bortezomib reduced GVHD severity was by diminishing production of the inflammatory cytokine IL-6 (discussed above).…”
Section: New Therapies In Clinical Trialsmentioning
confidence: 99%